Glasgow Anxiety Scale for people with an Intellectual Disability (GAS-ID): Development and psychometric properties of a new measure for use with people with mild intellectual disability - Mindham, J; Espie, C (2003)
Background. Self-rating scales are widely used in general adult practice; however, there is no reliable and valid method for assessing state anxiety in people with intellectual disability (ID). The present study describes the development and psychometric evaluation of a new scale, the Glasgow Anxiety Scale for People with an Intellectual Disability (GAS-ID). Methods. First, an item pool was generated from focus groups, a review of the literature and clinician feedback. Secondly, a draft scale was administered to 19 anxious and 16 non-anxious people with ID for further validation and appraisal of reliability. Thirdly, the scale was completed by 19 anxious, non-ID people for cross-validation with the Beck Anxiety Inventory (BAI). Finally, physiological concomitants were validated by pulse-oximetry. Results. The 27-item GAS-ID discriminated anxious from non-anxious participants, had good test-retest reliability (r=0.95) and internal consistency (α=0.96), and was reasonably correlated with the BAI (ρ=0.75). The correlation between the physiological subscale of the GAS-ID and changes in pulse rate was moderately significant (ρ=0.52). Conclusions. This preliminary study suggests that the GAS-ID offers a psychometrically robust and practical (5-10 min) approach to the appraisal of anxiety in this population.